KAJIAN STUDI KRITIS IMPLIKASI SLOGAN PAJAK “BANGGA BAYAR PAJAK” - Haryadi, Bambang; Zahra, Lailatuz (LP2M Institut Teknologi dan Bisnis Asia Malang, 2022)
The purpose of this study was to test the level of knowledge and understanding of taxpayers about tax slogans